Beginning ASP.NET 4 in C# 2010 - MacDonald, Matthew; Buckingham, Ewan.; Andres, Clay.; Anglin, Steve; Beckner, Mark.; Cornell, Gary.; Gennick, Jonathan; Hassell, Jonathan; Lowman, Michelle; Moodie, Matthew; Parkes, Duncan; Pepper, Jeffrey; et al. (Berkeley, CA : Apress, 2010)
The most up-to-date and comprehensive introductory ASP.NET book you$1 (Bll find on any shelf, Beginning ASP.NET 4 in C# 2010 guides you through Microsoft$1 (Bs latest technology for building dynamic web sites. Learn how to build sophisticated web pages quickly and easily using the most powerful tools available. Starting with the basics, this book provides exhaustive coverage of ASP.NET, guiding you from your first steps right through to advanced techniques - such as making database queries from within a web page, tuning your website for optimal performance and deploying your website to production servers. Within these pages, you$1 (Bll find tips for best practices and comprehensive discussions of key database and XML principles you need to know in order to be effective with ASP.NET. The book also fully explains the crucial coding techniques of object-orientation and code-behind on which your future as a successful ASP.NET developer relies.s
Introducing .NET -- The .NET Framework -- The C# Language -- Types, Objects, and Namespaces -- Developing ASP.NET Applications -- Visual Studio -- Web Form Fundamentals -- Web Controls -- Error Handling, Logging, and Tracing -- State Management -- Building Better Web Forms -- Validation -- Rich Controls -- User Controls and Graphics -- Styles, Themes, and Master Pages -- Website Navigation -- Working with Data -- ADO.NET Fundamentals -- Data Binding -- The Data Controls -- Files and Streams -- XML -- Website Security -- Security Fundamentals -- Membership -- Profiles -- Advanced ASP.NET -- Component-Based Programming -- Caching -- LINQ and the Entity Framework -- ASP.NET AJAX -- Deploying ASP.NET Applications.
Keywords: Computer science; Computer Science; Programming Techniques